Environmental stability of iron and zinc concentrations in grain of elite earlymaturing tropical maize genotypes grown under field conditions - Oikeh, S.O.; Menkir, A.; Maziya-Dixon, B.B.; Welch, R.M.; Glahn, Raymond P.; Gauch, G. (Cambridge University Press, 2004)
Assessment of the stability of micronutrients is important in breeding for the enhanced nutritional quality of staple food crops as a means to alleviate malnutrition. Twenty early-maturing elite tropical maize (Zea mays L.) genotypes were evaluated over 2 years at three locations representing three distinct agroecologies in West and Central Africa (WCA). The objectives were to analyse the pattern of genotype×environment interactions (GEI) and environmental stability of iron and zinc concentrations in grain using the Additive Main Effects and Multiplicative Interaction (AMMI) statistical model. Results indicated that the effects of genotypes, environments and GEI were significant (P<0·05) for both micronutrients. The effect of GEI was about double the contribution of the genotypes for grain iron and more than double the effect of genotypes for grain zinc. Partitioning of GEI indicated that variety×location was the dominant source of a significant amount of GEI for both micronutrients. Scores of the first two interaction principal component axes (IPCA1 and IPCA2) from the AMMI were significant and accounted for 0·68–0·75 of the pattern of GEI for both micronutrients. About half of the genotypes evaluated were stable for grain iron and zinc concentration over the set of environments. The AMMI model identified ACR98TZEMSR-W as the most stable genotype for grain iron and MAKA-SRBC5 was the most stable for grain zinc. However, the yellow genotype, AK94-DMR-ESR-Y was the most promising, with high and moderately stable concentrations of iron and zinc in the grain. Because it is yellow, with beta-carotene content and high concentrations of iron and zinc in the grain, it might significantly contribute to an improved intake of these micronutrients in populations who rely on maize for a major portion of their daily diet.